Exploring Queens' Iconic Identity and Advocacy Through Language in Drag Race Philippines - Tumenes, Clarizza Joy (International Journal of Language and Literary Studies, 2025)
This study investigated the linguistic strategies of drag queens in Drag Race Philippines Season 3 in constructing iconic identities and promoting advocacies using a qualitative research design. Grounded on Systemic Functional Linguistics’ (SFL) ideational metafunction using transitivity analysis, specifically relational, material, mental, and verbal processes, and field analysis was applied to examine the contestants’ oral interactions as captured in the show’s subtitles. Findings reveal that drag language is an interactive device for self-presentation, cultural representation, and activism. Relational processes indicate that drag queens construct individuality and cultural pride using humor, empowerment, and local reference. Material processes reveal the queens’ performance of creating identities, establishing drag as a profession and an artistic practice. Mental processes reflect introspection and resilience, while verbal processes reflect negotiation of self-concept, subversion of norms, and acceptance by society. The queens construct iconic identities through strategic linguistic selections that differentiate translocal and global drag cultures. Their language was for both self-representation and collective advocacy, addressing issues on LGBTQIA+ rights and gender equality, public health, and social justice, mixing personal narrative and social concerns. This study places the transgressive power of language in drag, subverting norms, diversity, and inclusivity in Philippine culture, at the center stage.